Koncepcje odbudowy powojennego Wrocławia 1945-1956 – między miastem prowincjonalnym a a drugą metropolią kraju - Dudek, Przemysław (Uniwersytet Wrocławski. Wydział, Prawa, Administracji i Ekonomii, 2013)
The article discusses the problem of Wroclaw status between 1945 and 1956. Combining historical and socio-political perspective, the author analyses different visions of reconstruction of the capital of Lower Silesia after World War II. The author shows how Wroclaw has been developing from a large regional city, through a tourist and cultural area, to the “capital of the Western Lands”, and how it gained metropolitan status. The article demonstrates economic, historical, political and social changes which have been influencing Wroclaw’s development. It discusses problems in the conceptualization of the status of the capital of Lower Silesia encountered at each stage of its development.
Keywords: metropolia; miasto prowincjonalne; Wrocław